The Container Thinks It’s Upside Down, and Other Stories of Automation - Lamontagne-Cumiford, Mathieu; Lillis, Hannah (Anthropologica)

(untitled) (University of Victoria, 2023)
A container cannot speak, but thanks to digitization and automation, it can now complain. The COVID pandemic and the pressures leveraged by its consequences on the global economy have brought sudden attention to the supply chain and the transport industry which powers it. While shortages and delays drew attention, industry players accelerated the digitization and automation of the industry. From the staging grounds of rail yards to warehouse floors, from the decks of massive container ships to the cubicles of office buildings, a concerted push for the automation of work is underway. Drawing on industry experience and interlocutors from a wide breadth of the logistics industry, we discuss the pressures and motivating factors that underpin this effort.